Interferon gamma immunoPET imaging to evaluate response to immune checkpoint inhibitors - Hackett, Justin B.; Ramos, Nicholas; Barr, Stephen; Bross, Madeline; Viola, Nerissa T.; Gibson, Heather M. (Frontiers in Oncology, 2023)
We previously developed a 89 Zr-labeled antibody-based immuno-positron emission tomography (immunoPET) tracer targeting interferon gamma (IFNγ), a cytokine produced predominantly by activated T and natural killer (NK) cells during pathogen clearance, anti-tumor immunity, and various inflammatory and autoimmune conditions.To evaluate [ 89 Zr]Zr-anti-IFNγ PET as a method to monitor response to immune checkpoint inhibitors (ICIs), CT26 tumor-bearing BALB/c mice were treated with combined ICI (anti-cytotoxic T-lymphocyte-associated protein 4 (CTLA-4) and anti-IFNγ PET imaging with immune checkpoint inhibitors 2 programmed death 1 (PD-1)). The [ 89 Zr]Zr-anti-IFNγ PET tracer, generated with antibody clone AN18, was administered during the ICI treatment course, with PET imaging 72 hours later. We detected significantly higher intratumoral localization of [ 89 Zr]Zr-anti-IFNγ in ICI-treated mice compared to untreated controls, while uptake of an isotype control tracer remained similar between treated and untreated mice.Interestingly, [ 89 Zr]Zr-anti-IFNγ uptake was also elevated relative to the isotype control in untreated mice, suggesting that the IFNγ-specific tracer might indicate underlying immune activity in situ in this immunogenic model. In an efficacy experiment, a significant inverse correlation between tracer uptake and tumor burden was also observed. Because antibodies to cytokines often exhibit neutralizing effects which might alter cellular communication within the tumor microenvironment, we also evaluated the impact of AN18 on downstream IFNγ signaling and ICI outcomes. Tumor transcript analysis using interferon regulatory factor 1 (IRF1) expression as a readout of IFNγ signaling suggested there may be a marginal disruption of this pathway. However, compared to a 250 µg dose known to neutralize IFNγ, which diminished ICI efficacy, a tracer-equivalent 50 µg dose did not reduce ICI response rates. These results support the use of IFNγ PET as a method to monitor immune activity in situ after ICI, which may also extend to additional T cell-activating immunotherapies.